Deep imaging of LepR+ stromal cells in optically cleared murine bone hemisections - Yuehan Ni; Jiamiao Wu; Fengqi Liu; Yating Yi; Xiangjiao Meng; Xiang Gao; Luyi Xiao; Weiwei Zhou; Zexi Chen; Peng Chu; Dan Xing; Ye Yuan; et al. (Bone Research)
Abstract Tissue clearing combined with high-resolution confocal imaging is a cutting-edge approach for dissecting the three-dimensional (3D) architecture of tissues and deciphering cellular spatial interactions under physiological and pathological conditions. Deciphering the spatial interaction of leptin receptor-expressing (LepR+) stromal cells with other compartments in the bone marrow is crucial for a deeper understanding of the stem cell niche and the skeletal tissue. In this study, we introduce an optimized protocol for the 3D analysis of skeletal tissues, enabling the visualization of hematopoietic and stromal cells, especially LepR+ stromal cells, within optically cleared bone hemisections. Our method preserves the 3D tissue architecture and is extendable to other hematopoietic sites such as calvaria and vertebrae. The protocol entails tissue fixation, decalcification, and cryosectioning to reveal the marrow cavity. Completed within approximately 12 days, this process yields highly transparent tissues that maintain genetically encoded or antibody-stained fluorescent signals. The bone hemisections are compatible with diverse antibody labeling strategies. Confocal microscopy of these transparent samples allows for qualitative and quantitative image analysis using Aivia or Bitplane Imaris software, assessing a spectrum of parameters. With proper storage, the fluorescent signal in the stained and cleared bone hemisections remains intact for at least 2–3 months. This protocol is robust, straightforward to implement, and highly reproducible, offering a valuable tool for tissue architecture and cellular interaction studies.